(untitled) (Web of Medicine: Journal of Medicine, Practice and Nursing, 2025)
The most important place in the laboratory diagnosis of infectious diseases is occupied by specific microbiological diagnostics, which is performed in bacteriological, virological, immunological and other laboratories. It consists of three stages: pre-analytical, analytical and post-analytical. The analytical stage includes microscopic, culture, biological, serological and allergological methods of microbiological diagnostics [4,8,9].